Shear-band thickness and shear-band cavities in a Zr-based metallic glass. (November 2017) - Liu, C.; Roddatis, V.; Kenesei, P.; Maaß, R.
Abstract: Strain localization into shear bands in metallic glasses is typically described as a mechanism that occurs at the nano-scale, leaving behind a shear defect with a thickness of 10–20 nm. Here we sample the structure of a single system-spanning shear band that has carried all plastic flow with high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and high-energy x-ray tomography (XRT). It is found that the shear-band thickness and the density change relative to the matrix sensitively depend on position along the shear band. A wide distribution of shear-band thickness (10 nm–210 nm) and density change (−1% to −12%) is revealed. There is no obvious correlation between shear-band thickness and density change, but larger thicknesses correspond typically to higher density changes. More than 100 micron-size shear-band cavities were identified on the shear-band plane, and their three-dimensional arrangement suggests a strongly fluctuating local curvature of the shear plane. These findings urge for a more complex view of a shear band than a simple nano-scale planar defect. Graphical abstract: Image 1